Temporal and spatial variability of ice cover occurrence on Carpathian rivers: a regional perspective - M. Fukś; Ł. Wiejaczka (Hydrology and Earth System Sciences)
This article presents an analysis of the temporal and spatial variability of ice cover (IC) occurrence from 1950 to 2020 in the Polish part of the Carpathians, with a focus on climatic conditions and the impact of reservoir operations. Data on border ice (BI), total ice cover (TIC), and air and water temperature were collected and analyzed using complementary statistical methods, such as Sen's slope, linear least-squares regression, the Mann–Kendall test, Student's t test, the Pettitt test, and the Mann–Whitney U test. Additionally, trends and tendencies across multiple time windows were analyzed through moving average and running trend analysis. The study found a decrease in the frequency of IC (the sum of the number of days with BI and TIC) and a transformation in the IC structure characterized by an increase in the number of days with BI and a significant decrease in the number of days with TIC. The results suggest that the observed changes in the ice regime of Carpathian rivers are primarily driven by warming winter air temperatures, and the effects are compounded by reservoir operations, which intensify the impact of climate change and significantly reduce IC occurrence downstream of their locations.